Legal Challenges and Consumer Protection Solutions in Online Insurance Purchases - Sihite, Sri Rumada; Hetharie, Yosia; Labetubun, Muchtar Anshary Hamid (Batulis Civil Law Review, 2026)
Introduction: The ease of access and efficiency offered, as well as the digital system, bring legal consequences that need to be studied in depth, specifically regarding the validity of the agreement, consumer protection, and the responsibilities of the parties. Purposes of the Research: This study aims to analyze the legal aspects of purchasing insurance in online transactions and the protection of online insurance buyers. Methods of the Research: This study uses a normative legal research method with a comparative approach. Research data is sourced from secondary materials, including documents on insurance purchases, Law Number 40 of 2014 concerning Insurance, the Civil Code, and relevant laws and regulations, legal literature, and scientific publications. Results Main Findings of the Research: The results of this study are online transaction purchases where the agreement is realized through a click – wrap agreement mechanism. Legally, this form of electronic agreement is recognized in the Electronic Information and Transactions Law, which states that electronic documents and signatures have valid legal force as long as they meet the specified requirements.